[(x: 5+9):7+7] x 3 – 25 = 5
{[(a - 2): 3 - 1]: 2-1} : 2 = 1
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
[(x:5+9):7+7]x3-25=5
[(x:5+9):7+7]X3=5+25
[(x:5+9):7+7]X3=30
[(x:5+9):7+7]=30:3
[(x:5+9):7+7]=10
(x:5+9):7=10-7
(x:5+9):7=3
(x:5+9)=3x7
(x:5+9)=21
x:5=21-9
x:5=12
x=12x5
x=60
{[(a-2):3-1]:2-1}:2=1
{[(a-2):3-1]:2-1}=1x2
{[(a-2):3-1]:2-1}=2
{[(a-2):3-1]:2}=2+1
{[(a-2):3-1]:2}=3
[(a-2):3-1]=3x2
[(a-2):3-1]=6
[(a-2):3]=6+1
[(a-2):3]=7
(a-2)=7x3
(a-2)=21
a=21+2
a=23
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă